Institutional Practices of Multicultural Islamic Education in Fostering Conscious Character and Peacebuilding - Siti Sumadiyah; Maskuri Maskuri; Junaidi Mistar (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Multicultural contexts pose persistent challenges to sustaining social harmony and peace, particularly within religiously and culturally diverse societies. While prior studies on Islamic education have largely emphasized theological and pedagogical dimensions, limited attention has been given to how institutional practices of multicultural Islamic education function as a transformative mechanism for character formation. This study investigates the enactment of five core values comprising taaruf, tawassuth, tasamuh, taawun, and tawazun within a non-formal adult training institution. The novelty of this research lies in its articulation of how management functions, namely Planning, Organizing, Actuating, and Controlling, are reconceptualized into experiential practices and neurospiritual mechanisms involving brainwave deceleration. Data were generated through sustained observation, in-depth interviews, and document analysis. The findings demonstrate that a conscious character emerges through a structured process where values are embedded in institutional routines and sustained through a collective habituation ecosystem, including digital social networks and ethical commerce. The study contributes to the field by articulating how multicultural Islamic education operates as an experiential institutional practice that links value-based habituation with peace-oriented character transformation in non-formal settings. These findings suggest that institutional practices, rather than abstract normative frameworks, play a decisive role in connecting Islamic educational values with peacebuilding outcomes.